Pengaruh Media Sosial dan Kesadaran Merek Terhadap Keputusan Pembelian Sepeda Motor Listrik di Kota Surabaya - Achmad Afandy; Cahya, Septyan Budy (Jurnal Pendidikan Tata Niaga (JPTN), 2025)
The development of technology today has experienced rapid progress in various sectors of life. Social media is a strategic platform to introduce a product to reach consumers. The implementation of this strategy is carried out by several electric motorcycle companies to gain brand awareness of electric motorcycle products. This study aims to determine the influence of social media and brand awareness on the purchase decision of electric motorcycles in the city of Surabaya. This type of research uses quantitative research with the population of Surabaya people who have made a decision to purchase an electric motorcycle. The data analysis technique used multiple linear regression which was processed using the SPSS (Statisstical Package for the Socio-Sciences) application. The results of this study indicate that social media and brand awareness have a simultaneous influence on the purchase decisions of electric motorcycles in Surabaya. Partially, social media has a significant effect on purchase decisions, as evidenced by a significance value of 0.036 and a t-value of 2.123, which exceeds the t-table value of 1.65. Likewise, brand awareness also shows a significant partial influence, with a significance value of 0.023 and a t-value of 2.298. These results confirm that both variables significantly affect purchase decisions, both collectively and individually. Keywords: Social Media; Brand awareness; Purchase Decision; Electric Motorcycle